Land Police and Family Farming in Minas Gerais in the XXI centure: the criation of SEDA - Gotlib, Joyce (Argumentos - Revista do Departamento de Ciências Sociais da Unimontes, 2024)
In this article, the background is the land dilemma in Minas Gerais province, throughout the investigation of the initiatives taking by the provincial government between 2015 and 2022 related to the agrarian field. Our central aim was mapping the effects promoted by the creation of SEDA-MG (Agrarian Development State Department) to achieve the Land Reform, with special look to the diversity of meanings that this expression assume for the different actors who participate and dispute resources in this ground. The study was made by bibliographycal and documental research, accessing primary and second hand font, and we also did interviews with SEDA employees. At the end, we argue, based on the data exposed here, that the increase of participation of activists, Landless People Movement militants and family farmers in Pimentel Government collaborated to enlarge the repertories of state action. However, the radicalization of disputes inside the State wasn’t enough to break the pattern of land reform hold by rural elite, which has a capitalist neoliberal stamp.